Competition in the International Niobium Market: An Econometric Study - Jáilison W. Silveira; Marcelo Resende (Center for Economic Studies and ifo Institute (CESifo), 2017)
Niobium is a highly strategic mineral, in which Brazil holds almost all of the world's reserves followed by Canada. Niobium has an important role in steel alloys for the aerospace industry and future potential for the industry's superconductors. The present paper investigates the prevailing market power in niobium at the country level by referencing the residual demand approach advanced by Goldberg and Knetter (1999). The empirical evidence for the American destination market indicates a significant market power for Brazil. However, despite Brazil's strong dominance in the supply of ferroniobium in comparison to Canada, it has moderate market power, which may suggest that other metals can have a relevant role in composing high performance alloys in terms of complementarity or substitution relationships.
Keywords: F14; L13; L61; 330; Niobium; residual demand; market power